The Impact of Workload and Work Environment on Outsourcing Workers' Job Satisfaction at PDAM Surya Sembada Surabaya's Pelayanan Teknis Timur Division - Rifqi Salwa Andhika; Mei Retno Adiwati (Digital Innovation : International Journal of Management, 2025)
This study examines job satisfaction among outsourcing employees in the Pelayanan Teknis Timur (PTT) Division of PDAM Surya Sembada Surabaya, with particular attention to the effects of workload and work environment. PDAM Surya Sembada Surabaya, a company specializing in the processing and distribution of clean water in Surabaya, frequently encounters job dissatisfaction attributed to excessive workload and suboptimal work conditions. A quantitative research design was implemented, utilizing structural equation modeling (SEM) with SmartPLS software for data analysis. Saturated sampling was applied, resulting in a sample of 57 respondents. The findings indicate that increased workload tends to reduce job satisfaction, while improvements in the work environment are associated with higher job satisfaction.